Hospital Resources: Persistent Reallocation under Price Changes - Florian Wozny (Institute of Labor Economics (IZA), 2020)
Changes in medical expenses may force hospitals to reallocate their resources, which potentially come at the detriment of healthcare quality. Using data on the universe of German hospitals, I investigate resource reallocations between capital stock, human resources, services and the organizational structure in case of reform-induced treatment price shocks at the hospital level. To identify a causal effect, I develop a unique identification strategy where I exploit hospitals' exposure to snowfall. A particularity of the reform led to exogenous treatment price shocks at hospital level in response to weather-induced excess of patients. The results show that higher prices induce hospitals to hire more physicians and nurses and encourage fewer mergers and privatization and less closures while not affecting the capital stock. In addition, hospitals become less specialized and reduce their treatment volume. These effects persist long after the treatment price shocks have vanished.
Keywords: I11; L10; L21; 330; hospital care; DRG; management